University partnerships for community and school system development - Cozza, Barbara; Blessinger, Patrick (Bingley, U.K. : Emerald, 2015)
This volume examines the diverse ways in which universities and colleges around the world are partnering and collaborating with other institutions to fulfil their missions and visions. University partnerships not only include collaborations between universities but also university-school (basic education) collaborative partnerships to improve local school systems. The increasing pressures to remove access and participation barriers, and to mitigate practices that restrict the free flow of education across borders, have created a growing global space for educational services of all types. As a result, traditional institutional boundaries have expanded to better respond to the increasing pressures placed on them by the growing demand for higher education services. The boundaries between educational institutions and other entities such as government, business, and non-profit organizations have become more fluid which has resulted in increased involvement by institutions, faculty, and students in activities outside the traditional boundaries of the classroom. This edited volume will specifically explore university partnerships for community and school system development.
Innovative approaches in university partnerships : an introduction to university partnerships for community and school system development / Barbara Cozza, Patrick Blessinger -- University-school partnership in the framework of informal education / Monika Eriksen, Kinga Anna Gajda -- Service-based initiatives in teacher education : bridging communities and universities through field experiences / Sheri C. Hardee -- Supporting the expansion of pre-primary education in Ethiopia : a collaboration between an Ethiopian and a UK higher education institution / Valerie Huggins, Takele Tadesse, Tesfaye Tadesse -- Extending school communities through university-school partnerships / Sharon M. Peck -- Building greater capacity in science education : a partnership between a secondary science school and a research-intensive university / Gerry Rayner, Peter Corkill -- Creating a healing campus : a partnership between a university and a provider of mental health services / Nick Rowe -- Enhancing global competencies through international partnerships in elementary schools / Cherry O. Steffen, Stacy Delacruz, Gwen McAlpine -- Knowledge that brings us together : university/school district partnerships to improve K-12 ELL instruction / Tricia Valdez-Zontek, Teddi Beam-Conroy, Nancy Encarnacio<U+0301>n -- Changing demographics : using university-school partnerships to support the instruction of culturally and linguistically diverse student populations / Tymika Wesley -- Distributed leadership in a university-school collaborative partnership to build the STEM pipeline for girls / Jennifer W. Shewmaker, Sarah K. Lee -- Focus west : a successful inter-institutional, multi-agency partnership to improve school pupils' access to higher education / Stephanie McKendry, Bernadette Sanderson, Chloe Dobson -- University, school, territory : strategies and activities of inter-institutional partnerships of the degree course in sciences of primary education / Antonella Nuzzaci -- Hunting dragons : an organic, multidisciplinary pedagogy / Lisa G. Stoneman, DorothyBelle Poli, Alton C. Dooley, Jr. -- Synergistic benefits and cultural competencies in a multidisciplinary PDS partnership / Helja<U+0308> Antola Crowe, Robert Wolffe, Jana Hunzicker.
Includes indexes.
Print version record
Keywords: Education -- Higher; Higher & further education, tertiary education; Community and college; Community and school; Universities and colleges -- Public services; Universities and colleges -- Public relations; Education and state